(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
The kinetics and mechanism of the reacions of anesthesin with pyridoxal and glucose were studied. Under comparable conditions, the condensation of anesthesin with pyridoxal and glucose includes two kinetically different steps. The first fast step is addition of the anesthesin to pyridoxal and glucose with of the corresponding amino alcohol, the second (slower) step is dehydration of the amino alcohol to give Schift base and N-glycosylamines. The scheme of anesthesin with pyridoxal and glucose is proposed.